Epidemiology and Clinical Management of Early Childhood Caries in Israel - Shmueli, Aviv; Moskovitz, Moti; Halperson, Elinor; Ram, Diana; Fux-Noy, Avia (Frontiers in Public Health, 2019)
Aim: The aim of the present review is to describe the current status of early childhood caries (ECC) in Israel in aspects of epidemiology, prevention, and management. Methods: PubMed search was performed using the words caries, children, Israel. Demographic data was collected from the Israeli Central Bureau of Statistics. Results: The decayed, missing, and filled teeth index was 2.72 in 1992 and 2.56 in 2016. The proportion of restored teeth has increased. A number of preventive programs are ongoing but a general preventive program is lacking at the national level. From 2010, every child in Israel is eligible to receive free dental treatment. Conclusion: The gaps in understanding of the epidemiological profile of ECC in Israel is a call for more research conduct on ECC in the country.